(untitled) (JOISCO: Journal of Islamic Communication, 2026)
This study examines the political communication strategies implemented by three West Kalimantan gubernatorial candidates, Sutarmidji, Rian Norsan, and Muda Mahendrawan through their official Instagram accounts. The main objective of the study is to identify the use of Instagram as a communication medium for political actors in West Kalimantan. This study uses a qualitative research type with a content analysis approach, where the main data is obtained from observation of uploaded content, documentation, and literature studies. The three Instagram accounts, namely @bang.midji, @rianorsan.id, and @muda.mahendrawan, a content analysis approach was chosen to study the visual elements, messages, and connectedness built through the campaign content of the three West Kalimantan gubernatorial candidates. The results of the study show that the candidates in utilizing Instagram with different strategies, including the @bang.midji account building credibility and a competent leadership image through uploading information on work programs and achievements during their previous term supported by high credibility, then the @rianorsan.id account focuses on building emotional connections through direct interaction with the community, Meanwhile, the @muda.mahendrawan account shows very high upload activity, but with a relatively lower level of audience interaction compared to other candidates. This research is expected to contribute to the digital political communication literature by offering specific insights into the use of Instagram in regional head elections